Factores internos que inciden en el clima organizacional en las cooperativas de ahorro y crédito Virgen del Cisne y Visión de los Andes. - Oña Velásquez, Luz Estefanía (2018)
In the present research project, the internal factors determinants in the organizational climate of the collaborators of the COAC's Virgen del Cisne and Visión de los Andes were determined. Considering that at present the organizations do not take into account the welfare of the collaborators, thus causing a low performance in their activities. The main objective of the research is to detect the shortcomings that exist in aspects such as: autonomy, pressure, help and innovation at the same time the dimensions of the organizational climate were investigated, such as: internal communication, recognition, interpersonal relationships, decision making, environment physical and adaptation to change, which are fundamental pillars for public and private organizations. Therefore, it was necessary to carry out the fieldwork, through the type of descriptive and documentary research, which allowed us to correctly describe the current situation of the aforementioned organizations, with the quantitative approach allowed the numerical measurement and the statistical analysis was carried out. applied the survey technique whose measurement instruments were from the authors Koys & Decottis (internal factors); Chiang, Nuñez and Salazar (organizational climate dimensions). The results obtained from the application of the questionnaire were analyzed by applying the Chisquare statistic and the Logit Model in the SPSS program, verifying the relationship between autonomy and pressure on internal communication, decision-making, the degree of association measured Through the coefficient of contingency thrown as a result that the pressure factor affects internal communication in 57.60%, the autonomy factor affects decision making in 29.20%. Using the Logit statistical model, we contrasted the previous results, verifying an inversely proportional relationship in internal communication and decision making and the factors autonomy and pressure.